1991
DOI: 10.3354/cr001145
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of wheat ontogenesis. I. Appearance of main stem leaves in the field

Abstract: Rate of leaf appearance differs among wheat crops sown in the field at different dates. This can be interpreted either as a direct effect of the date of sowing on the rate of leaf appearance or as a n indirect effect of an ontogenetic decline in the rate of appearance. Analysis of data from both laboratory and field experiments led to the conclusion that the second hypothesis is more reliable. A simulation model of leaf appearance was formulated on the basis of this hypothesis, and tested using experimental re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0
3

Year Published

1996
1996
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 16 publications
1
24
0
3
Order By: Relevance
“…Within the most relevant phenophases, leaf appearance has been particularly stressed, and the relationships with environmental factors have been studied in wheat and barley with the aim to understand the dynamics of the leaf area development intercepting solar radiation (Kirby et al, 1985;Kirby, 1990;Hay and Kirby, 1991;Miglietta, 1991a). Kirby (1990) has shown that apical meristematic tissue development and leaf appearance are strictly related.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Within the most relevant phenophases, leaf appearance has been particularly stressed, and the relationships with environmental factors have been studied in wheat and barley with the aim to understand the dynamics of the leaf area development intercepting solar radiation (Kirby et al, 1985;Kirby, 1990;Hay and Kirby, 1991;Miglietta, 1991a). Kirby (1990) has shown that apical meristematic tissue development and leaf appearance are strictly related.…”
Section: Introductionmentioning
confidence: 99%
“…Under both growth chambers and field conditions it has been shown that the phyllochron (PhL) greatly varies with sowing dates (Baker et al, 1980;Kirby and Perry, 1987;McMaster et al, 1992), main stem leaf number (Miglietta, 1991a), phenological stage (Baker et al, 1986;Boone et al, 1990;Jamieson et al, 1995), and genotype (Frank and Bauer, 1995). Other variables, such as soil temperature close to the shoot apex, have been suggested to improve prediction of the PhL in wheat .…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the above, Miglietta (1989Miglietta ( , 1991a postulated that rate of leaf appearance would likely depend on ontogeny and hence on the timing of leaf initiation at the stem apex and the duration of leaf tip elongation through the whorl of the mature sheaths (Hay and Kemp 1990;Skinner and Nelson 1995). However, neither this model, nor those that are based on conditions at the time of emergence are, according to Kirby (1995) completely satisfactory in explaining the variation among sowing dates.…”
mentioning
confidence: 96%
“…Desse modo, para bainhas maiores, haveria maior trajeto a ser percorrido pela folha no interior do pseudo-colmo e a TAP seria, então, reduzida (Garcez Neto et al, 2002). Outro fato importante relativo à redução da taxa de aparecimento de folhas do perfilho é sua dependência do avanço da idade da planta, uma vez que a distância a ser percorrida pela folha em expansão eleva sucessivamente com o aparecimento de cada folha (Miglietta, 1991). Portanto, não seria correto afirmar que o capim-setária, em comparação às demais gramíneas avaliadas, é mais sensível ao déficit hídrico, por apresentar valores de filocrono superiores aos das gramíneas estoloníferas.…”
Section: Figura 2 -Phyllochron Of Individual Leaves (Phyl Days Leaftunclassified